2022
DOI: 10.3390/app12073238
|View full text |Cite
|
Sign up to set email alerts
|

Strength, Flexibility and Postural Control of the Trunk and Lower Body in Participants with and without Patellofemoral Pain

Abstract: Patellofemoral pain (PFP) is a frequent knee condition. The aim of this study was to investigate strength, flexibility and postural control in people with and without PFP. Fifty-five participants between 14 and 54 years of age (PFP = 18, control group = 37) were included. Strength and flexibility for all trunk, hip, knee and ankle muscle groups were measured along with postural control outcomes. Analyses were conducted based on the “affected” and “non-affected” leg within-group and between-groups. Between-grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“… Risk of bias: The mean EIA score was 1.2 (0.3), with 75% of included studies presenting low RoB ( n = 21), and 25% presenting high RoB ( n = 7) (Additional file 6 ). Anteroposterior (AP) postural stability (19 studies [ 24 , 25 , 30 , 85 100 ] ): Very low level evidence indicated that people with PFP present worse AP balance with a large effect compared to controls (SMD 1.03, 95% CI 0.40–1.66; Fig. 2 and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Risk of bias: The mean EIA score was 1.2 (0.3), with 75% of included studies presenting low RoB ( n = 21), and 25% presenting high RoB ( n = 7) (Additional file 6 ). Anteroposterior (AP) postural stability (19 studies [ 24 , 25 , 30 , 85 100 ] ): Very low level evidence indicated that people with PFP present worse AP balance with a large effect compared to controls (SMD 1.03, 95% CI 0.40–1.66; Fig. 2 and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meta-regression indicated that age is not a source of heterogeneity (Additional file 7 ). Mediolateral (ML) postural stability (13 studies [ 24 , 29 , 58 , 86 92 , 96 , 99 , 100 ] ): Moderate level evidence indicated that people with PFP present worse ML balance with a large effect compared to controls (SMD 0.87, 95% CI 0.31–1.42; Fig. 3 and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations